Self-expanding nitinol renal artery stents: comparison of safety and efficacy of bare versus polyzene-F nanocoated stents in a porcine model - Kurz, Patrick; Stampfl, Ulrike; Christoph, Patricia; Henn, C.; Satzl, Stefanie; Radeleff, Boris; Berger, Irina; Richter, Götz Martin (CardioVascular and interventional radiology, 2011)
To investigate the safety and efficacy of a Polyzene-F nanocoat on new low-profile self-expandable nitinol stents in minipig renal arteries.